2008
DOI: 10.1111/j.1467-7717.2008.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Unauthorised development and seismic hazard vulnerability: a study of squatters and engineers in Istanbul, Turkey

Abstract: Many cities in developing nations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 39 publications
3
22
0
2
Order By: Relevance
“…Public distrust of expert seismic adjustment advice arises when acts of the Turkish construction industry, engineers and regulatory bodies are seen to be corrupt (Green, 2008). Members of households feel that these entities have betrayed the wider society by knowingly and willingly letting monetary and political benefits take precedence over diligence and moral integrity.…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Public distrust of expert seismic adjustment advice arises when acts of the Turkish construction industry, engineers and regulatory bodies are seen to be corrupt (Green, 2008). Members of households feel that these entities have betrayed the wider society by knowingly and willingly letting monetary and political benefits take precedence over diligence and moral integrity.…”
Section: Trustmentioning
confidence: 99%
“…House-building is therefore contracted out to people who are perceived to be noncorrupt and competent (but often are not), undertaken by the prospective owners themselves, or proceeds as a mix of the two. Green (2008) proposes that Istanbul's extensive selfbuilt housing stock increases the vulnerability of its citizens, and that lack of trust between lay and expert groups is partly to blame.…”
Section: Trustmentioning
confidence: 99%
“…Levels of trust in the competence and moral integrity of political, civic, voluntary, scientific, and industrial actors in emergency management have been shown to influence seismic adjustment behavior. Trust in the competence of expert agencies and political elites promotes uptake of adjustments (Paton et al 2010), while active distrust of those involvedfor example, due to perceptions of corruption-undermines it (Green 2008). Thus, the level of trust people have in such agents and institutions shapes their orientations toward engaging in adjustment behavior.…”
Section: Past Psychological Studies Of Earthquake-prone Areasmentioning
confidence: 99%
“…Although self‐construction may be the most viable option for many disaster‐affected households, it is also likely to be the most hazardous. When affected communities build back themselves, it is common for construction processes to include the same inadequate building practices as before, and for the repaired or rebuilt homes to leave householders at risk from future disasters (Coburn and Spence, ; Green, ; Parrack, Flinn, and Passey, ). The likelihood of householders incorporating safer construction methods in the rebuilding of their homes can be affected by many factors, including a lack of understanding of safer building methods (Yahya et al, ; Schilderman, ; Powell, ; Maynard and Barritt, ), the prohibitive expense of including additional hazard‐resistant construction techniques (Tran Tuan et al, ), the financial and technical support available, or the required level of compliance with local building codes (Twigg et al, ).…”
Section: Post‐disaster Shelter Programmes: Supporting Self‐recovery Amentioning
confidence: 99%